2003
DOI: 10.1007/s00299-002-0529-x
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium tumefaciens-mediated transformation of wheat using a superbinary vector and a polyamine-supplemented regeneration medium

Abstract: Immature embryo-derived calli of spring wheat (Triticum aestivum L.) cv Veery5 were transformed using Agrobacterium tumefaciens strain LBA4404 carrying either binary vector pHK22 or superbinary vector pHK21, the latter carrying an extra set of vir genes--vir B, -C and -G. In both cases, transient beta-glucuronidase ( GUS) expression ranging from 35-63% was observed 3 days after co-cultivation, but 587 calli infected with pHK22/LBA4404 failed to produce a single stably transformed plant, whereas 658 calli infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 25 publications
4
52
0
1
Order By: Relevance
“…In the present study, a 3-day co-cultivation period was found to be optimum for maximum transformation frequency. Similar results were also reported earlier in other species (Hu et al 2002;Khanna et al 2003).…”
Section: Factors Affecting Transformation Frequencysupporting
confidence: 94%
“…In the present study, a 3-day co-cultivation period was found to be optimum for maximum transformation frequency. Similar results were also reported earlier in other species (Hu et al 2002;Khanna et al 2003).…”
Section: Factors Affecting Transformation Frequencysupporting
confidence: 94%
“…Biolistics can also be utilised to deliver DNA into the genomes of mitochondria and chloroplasts. Perceived advantages, particularly in terms of lower copy number have driven significant research into using Agrobacterium tumefaciens (synonym Rhizobium radiobacter) for the DNA transfer process, and many laboratories now report successful wheat transformation using Agrobacterium (Binka et al 2012;Campa et al 2005;Cheng et al1997;Cheng et al 2003;Ding et al 2009;Guo et al 1998;Haliloglu and Baenziger 2003;Hamid et al 2012;He et al 2010;Jones et al 2005;Khanna and Daggard 2003;Mahalakshmi and Khurana 1995;Marks et al 1989;McCormac et al 1998;Mitic et al 2004;Mooney et al 1991;Murin et al 2011;Parrott et al 2002;Patnaik et al 2006;P茅rez-Pi帽eiro et al 2012;Przetakiewicz et al 2004;Pukhalskii et al 1996;Rashid et al 2012;Shi et al 2011;Song et al 2012;TamasNyitrai et al 2012;Trifonova et al 2001;Wu et al 2003Wu et al , 2008Xia et al 1999). One particular unpublished method developed by the Japan Tobacco company (PureWheat Technology) has been licensed to specific laboratories who report wheat transformation efficiencies of more than 50 %.…”
Section: Methods For Wheat Transformationmentioning
confidence: 98%
“…It has been successfully developed only for the agronomically important wheat (Cheng et al 1997;Hu et al 2003;Khanna and Daggard 2003;Wu et al 2003;Przetakiewicz et al 2004) and more recently for triticale (Nadolska-Orczyk et al 2005). Oat (Avena sativa L.) is another allohexaploid species thus far transformed only via the biolistic method.…”
Section: Introductionmentioning
confidence: 99%